2016
DOI: 10.3390/ma9080701
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mechanical and Bactericidal Properties of Cement Mortars Containing Waste Glass Aggregate and Nanomaterials

Abstract: The recycling of waste glass is a major problem for municipalities worldwide. The problem concerns especially colored waste glass which, due to its low recycling rate as result of high level of impurity, has mostly been dumped into landfills. In recent years, a new use was found for it: instead of creating waste, it can be recycled as an additive in building materials. The aim of the study was to evaluate the possibility of manufacturing sustainable and self-cleaning cement mortars with use of commercially ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 60 publications
4
54
0
1
Order By: Relevance
“…The decision to use a geopolymer mortar with glass to measure the bactericide capacity of the geopolymers was based on the results reported by Mejía de Gutiérrez et al [41], who observed a higher photocatalytic efficiency for B-rhodamine degradation in compounds functionalized with TiO 2 when glass waste was used to prepare the geopolymer mortars. Likewise, studies by Sikora et al [35] showed that the use of glass enhanced the photocatalytic activity for E. coli colony degradation, and elimination occurred in 30 min.…”
Section: Assays With Bacteriamentioning
confidence: 91%
See 1 more Smart Citation
“…The decision to use a geopolymer mortar with glass to measure the bactericide capacity of the geopolymers was based on the results reported by Mejía de Gutiérrez et al [41], who observed a higher photocatalytic efficiency for B-rhodamine degradation in compounds functionalized with TiO 2 when glass waste was used to prepare the geopolymer mortars. Likewise, studies by Sikora et al [35] showed that the use of glass enhanced the photocatalytic activity for E. coli colony degradation, and elimination occurred in 30 min.…”
Section: Assays With Bacteriamentioning
confidence: 91%
“…The results reported in this study corresponding to GP and GP-G are satisfactory. The toxicity of nanoparticles for inhibiting bacterial growth was previously demonstrated for S. aureus using ZnO nanoparticles by Sikora [35], and for E. coli using CuO by Kumar [20] and TiO 2 by Sunada et al [50]. Sunada et al [50] explained that the photokilling reaction of E. coli cells using TiO 2 is initiated by a partial decomposition of the outer membrane, followed by an attack of the cytoplasmic membrane, resulting in cell death.…”
Section: Assays With Bacteriamentioning
confidence: 96%
“…In the recent studies by Sikora et al [8] and Chung et al [9], it was reported that nanosilica can have a beneficial effect on the decrement of sorptivity and thermal conductivity of cement mortars as well as concretes containing waste glass, in comparison to conventional cement-based composites with natural aggregate. In addition, it was reported that the incorporation of nanosilica contributed to a noticeable improvement in the mechanical properties of cement mortars containing waste glass aggregate [10].…”
Section: E3s Web Of Conferences 49mentioning
confidence: 99%
“…e incorporation of additions to modify and improve its fresh properties and its physical, mechanical, and durability properties, as well as to obtain new functional properties such as photocatalysis [1,2], antibacterial effects (Sikora et al [3,4]), hydrophobicity (Tittarelli [5] and Nunes and Slizkova [6]), and fungicide effects (De Muynck et al [7]) among others is currently an important research topic. In recent years, nanotechnology applied to cement-based materials has been growing since the use of additions of nanometric size significantly increases the effects on their mechanical and functional properties, and the combination of several additions might be very promising (Sikora et al [4], León et al [8], and Mohseni et al [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Arliguie showed that the delay in hydration is due to the precipitation of an amorphous Zn(OH) 2 layer around the anhydrous C 3 S grains which inhibits cement dissolution (Arliguie and Grandet [31]). e hydration of C 3 A in the presence of ZnO occurs too, when there is a significant presence of SO 3 [33]). Johnson and Kersten showed that solid solution is a possible binding mechanism for Zn(II) in the CSH gel, indicating that at least 10% of Zn may be incorporated in the CSH structure (Johnson and Kersten [34]).…”
Section: Introductionmentioning
confidence: 99%